American literary realism, critical theory, and intellectual prestige, 1880-1995 - Barrish, Phillip (Cambridge studies in American literature and culture, 2001)
Focusing on key works of late nineteenth and early twentieth-century American literary realism, Barrish traces the emergence of new ways of gaining intellectual prestige and some degree of cultural recognition. This book is the first extended treatment of a genre, realism, central to our understanding of American literature.